2016
DOI: 10.1063/1.4943977
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight graphene nanoplatelet/boron carbide composite with high EMI shielding effectiveness

Abstract: Lightweight graphene nanoplatelet (GNP)/boron carbide (B4C) composites were prepared and the effect of GNPs loading on the electromagnetic interference (EMI) shielding effectiveness (SE) has been evaluated in the X-band frequency range. Results have shown that the EMI SE of GNP/B4C composite increases with increasing the GNPs loading. An EMI SE as high as 37 ∼ 39 dB has been achieved in composite with 5 vol% GNPs. The high EMI SE is mainly attributed to the high electrical conductivity, high dielectric loss as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Moreover, elemental metal powder-derived MAX materials have demonstrated to be effective reinforcement in TiB2 [39][40][41] , Al2O3 [42][43][44] composites with enhanced mechanical properties by in situ reaction. More recently, as explicated in our previous work [45][46][47][48][49] , titanium aluminum carbide (Ti3AlC2) was chosen as an effective sintering aid to effectively densify B4C ceramics with enhanced sintering ability and mechanical performance simultaneously. High hardness and toughness values of 28.5GPa and 7.02 MPa .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elemental metal powder-derived MAX materials have demonstrated to be effective reinforcement in TiB2 [39][40][41] , Al2O3 [42][43][44] composites with enhanced mechanical properties by in situ reaction. More recently, as explicated in our previous work [45][46][47][48][49] , titanium aluminum carbide (Ti3AlC2) was chosen as an effective sintering aid to effectively densify B4C ceramics with enhanced sintering ability and mechanical performance simultaneously. High hardness and toughness values of 28.5GPa and 7.02 MPa .…”
Section: Introductionmentioning
confidence: 99%
“…Looking into various reports [20][21][22][23][24][25][26][27][28] on materials done earlier, the underneath science was understood. Similar system, such as of PVDF/MWCNT has been studied by G.S.…”
Section: Aip Advances 6 065107 (2016)mentioning
confidence: 99%
“…[18][19][20][21] Change in ε ′ (and further Tan δ) from positive to negative after percolation threshold is due to induction polarization. [23][24][25][26][27] To further evaluate the SE data for all samples and to check whether the high SE is due to reflection and /or absorption, the raw data was again looked into. It was found that, with the incorporation of various wt% of MWCNT in the PVDF, the absorption parameter increased concomitantly in the 5 wt% sample and above, as compared to the reflection contribution.…”
Section: Aip Advances 6 065107 (2016)mentioning
confidence: 99%
“…Moreover, elemental metal powder-derived MAX materials have demonstrated to be effective reinforcement in TiB 2 [40][41][42], Al 2 O 3 [43-45] composites with enhanced mechanical properties by in situ reaction. More recently, as explicated in our previous work [46][47][48][49][50], titanium aluminum carbide (Ti 3 AlC 2 ) was chosen as an effective sintering aid to effectively densify B 4 C ceramics with enhanced sintering ability and mechanical performance simultaneously. High hardness and toughness values of 28.5 GPa and 7.02 MPa·m 1/2 respectively were achieved for B 4 C composites sintered with 20 vol.% Ti 3 AlC 2 at 1900 • C. The mechanisms of the enhanced sinterability of high-performance ceramics in previous works [1,10,[46][47][48][49][50] could be classified into two aspects: Firstly, the decomposed metals from Ti 3 SiC 2 or Ti 3 AlC 2 at high-temperature can form liquid phase which promote sintering effectively.…”
mentioning
confidence: 99%
“…The main competitive advantage of MAX aids is considered to be formation of reaction bonding between Si 3 N 4 matrix and aids, rather than intergranular glassy phase. Motivated by such an idea [46][47][48][49][50], these non-oxides cermets are highly expected to play a multifunctional role in densification and enhancement of mechanical properties of Si 3 N 4 ceramics.It is also noteworthy that Al decomposed from Ti 3 AlC 2 and residual O originated from raw Si 3 N 4 powders would be dissolved into Si 3 N 4 grains during high-temperature sintering procedure, which is harmful to the purity and thermal performance of Si 3 N 4 -based ceramics. As Y. Zhou et al.…”
mentioning
confidence: 99%